Performance of Typically Developing Four- and Five-Year-Old Children with AAC Systems using Different Language Organization Techniques. - Light, Janice; Drager, Kathryn; McCarthy, John; Mellott, Suzanne; Millar, Diane; Parrish, Craig; Parsons, Arielle; Rhoads, Stacy; Ward, Maricka; Welliver, Michelle (AAC: Augmentative & Alternative Communication, 2004)
In this paper, the results of two studies designed to investigate the learning demands of four different approaches to the layout and organization of language in electronic augmentative and alternative communication (AAC) systems are presented: taxonomic grid, schematic grid, schematic scene, and iconic encoding techniques. A total of 80 typically developing children participated in the two studies: 40 four-year-olds (Study 1) and 40 five-year-olds (Study 2). Ten children in each study were randomly assigned to each of the four system organization conditions. The children were introduced to target vocabulary items (24 items for the 4-year-olds and 30 for the 5-year-olds) in a series of four learning and testing sessions. Half of the vocabulary items were concrete concepts and half were abstract concepts. Results of the studies indicated that the 4-year-old and 5-year-old children were more accurate locating target vocabulary in the three dynamic display conditions (taxonomic grid, schematic grid, schematic scene) than in the iconic encoding condition. On initial exposure to the systems, the iconic encoding technique was not at all transparent to the children; the other three systems were only moderately transparent. All but one of the 4-year-old children and all of the 5-year-old children demonstrated gains in accuracy across the learning sessions; gains were significantly greater for the three dynamic display conditions than for the iconic encoding condition. The children were more accurate with the concrete vocabulary items than the abstract ones. There was some, albeit limited, evidence that the children generalized to facilitate learning of novel vocabulary items. Results are discussed with reference to the literature. Implications for practice and directions for future research are also discussed.